Vegetation and lithologic influences on channel morphology in the southwestern U.S. - Wieting, Celeste, author; Rathburn, Sara, advisor; Wohl, Ellen, committee member; McGrath, Dan, committee member; Morrison, Ryan, committee member; Friedman, Jonathan, committee member (Colorado State University. Libraries, 2024)
Vegetation and lithology play critical roles in shaping landscapes, creating diverse river and gully morphologies. Vegetation stabilizes banks and alters flow dynamics. In the Southwestern United States, non-native, invasive plant species contributed to regional trends of river channel narrowing and simplification and degraded diverse riparian habitats throughout the 20th century. More recently, efforts to remove invasive riparian vegetation (IRV) have been widespread, especially since 1990. Restoration practitioners who perform IRV treatments often focus on wildlife or vegetation response; however, geomorphic processes should be considered in restoration planning because they drive flow, sediment transport, and aquatic habitat and vegetation dynamics, and because of the potential for damage to downstream people and infrastructure. Depending on the restoration goal, management practices can be used to enhance or minimize the increase in channel dynamism caused by IRV removal. At the river reach scale, I investigated biogeomorphic feedbacks at one of the 15 previously analyzed study sites, the Rio Grande in Texas. Along the Rio Grande in Big Bend National Park (BIBE), restoration goals to remove invasive giant cane (Arundo donax) include decreasing channel narrowing and increasing water and sediment conveyance. Recent work has indicated that removal of giant cane has successfully reduced its extent, but the geomorphic effects of giant cane treatment and subsequent revegetation are still not well understood. A general lack of reach-scale studies of riparian plant pronation during flow inundation and the biogeomorphic feedbacks between plants, flow, and sediment transport contribute to this knowledge gap. I quantified morphological-effect plant traits for three common riparian plant species: invasive giant cane, native baccharis (Baccharis salicifolia), and native phragmites (Phragmites australis). I collected data at the plant, plot, and reach scales and created upright and flexible frontal area and vegetation roughness curves using photographs of plants and stem counts of plots. Then, I used these data in a reach-scale 2D hydraulic model to simulate species-specific effects and the effects of giant cane removal on channel hydraulics. Results indicate that the mean vegetation roughness is similar for all three species at the plant scale, but at the plot scale, vegetation roughness is higher for giant cane and phragmites due to higher stem densities. Hydraulic modeling results suggest that vegetation increased velocities in the center of the channel and decreased velocities on the channel margins. When all the vegetation was represented as giant cane, reach-scale water surface elevations were the highest and reach-scale velocities the lowest. Removing giant cane decreased water surface elevations, indicating increased conveyance. To determine the effects of IRV removal on a regional scale across the Southwest U.S., treated and untreated reaches at 15 sites along 13 rivers were compared before and after IRV treatment using repeat aerial imagery to assess long-term (~10 year) channel change. Resolving observations of channel change into separate measures of floodplain destruction and formation provided more information on underlying processes than simple measurements of channel width and centerline migration rate. IRV treatment significantly increased channel width and floodplain destruction. Treated reaches had higher floodplain destruction than untreated reaches at 14 of 15 sites, and IRV treatment increased floodplain destruction by a median factor of 1.9. The effect of treatment increased with the stream power of the largest flow over the study period. From the results, I suggest that restoration managers consider the system's susceptibility to change, downstream threats, and desired process changes when defining their geomorphic restoration goal because treatment of a dominant species over a large area can be expected to have major fluvial geomorphic consequences. In addition to vegetation, the lithology and surficial sediment properties influence hydrological processes, sediment transport, and gully and channel morphology. In semi-arid environments where vegetation is lacking, and precipitation is sufficient to drive erosion, sediment yields tend to be greatest. Increased landscape erosion is predicted as more extreme weather causes frequent or intense rainfall, and flooding. In Wupatki National Monument (WUPA), heavy rainstorms over the past decade, lack of vegetation, and presence of unconsolidated volcanic-derived cinders expose archaeological sites to erosion, a concern to cultural resource managers. To identify archaeological sites of highest vulnerability to erosion, I analyzed gully morphologic change over a 5-year period. I found that 35 measured gullies are actively eroding, with statistically significant changes in gully depth from 2016 to 2021. Up to 0.5 m of incision was documented over a five-year period. A structure-from-motion analysis at the hillslope scale confirmed gully morphological changes and supports the applicability of conducting similar analyses on a larger scale. More erosion occurred in gullies with catchments predominantly covered with cinders because of cinder mobility. A weak relationship was noted between gully catchment area and gully head slope, likely related to runoff processes from outcrops of resistant sedimentary rocks forming cliffs and characteristics of cinders that maximize infiltration and transport. Based on assessment of gully morphologic change and substrate characteristics, 22 archaeological sites along Wupatki Wash were identified as having a high vulnerability to erosion.
Keywords: erosion; invasive riparian vegetation; channel change; river restoration; hydraulic modeling